PENGARUH KAPASITAS FISKAL DAERAH DAN PERTUMBUHAN EKONOMI DAERAH PADA INDEKS PEMBANGUNAN MANUSIA - Widani, Cok Istri Krisnanda; Erawati, Ni Made Adi (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This study aims to identify, analyze and obtain empirical evidence about the influence of local fiscal capacity (with the PAD parameter, DAU, DBH) and local economic growth in the HDI in the district / city of Bali province. The research covers eight counties and one city in the province of Bali within the period of observation 2008-2013. The sample used in this study is saturated samples (whole population is used as a sample). This study used secondary data obtained from the Finance Bureau and Badap Bali Provincial Bureau of Statistics. Data analysis techniques used include: classical assumption test, test the coefficient of determination, the F test and t test. The test results indicate that the PAD and DAU and no significant negative effect on the HDI, whereas DBH is positive but not significant effect on the HDI, and the Regional Economic Growth positive and significant impact on the HDI District / City of Bali Province.
Keywords: PAD, DAU, DBH, PED, IPM